2011
DOI: 10.1007/s00198-011-1656-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading-related changes in osteocyte sclerostin expression in mice are more closely associated with the subsequent osteogenic response than the peak strains engendered

Abstract: SummaryOsteocyte sclerostin is regulated by loading and disuse in mouse tibiae but is more closely related to subsequent local osteogenesis than the peak strains engendered.IntroductionThe purpose of this study was to assess the relationship between loading-related change in osteocyte sclerostin expression, local strain magnitude, and local bone modeling/remodeling.MethodsThe right tibiae of 19-week-old female C57BL/6 mice were subjected to non-invasive, dynamic axial loading and/or to sciatic neurectomy-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
198
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(218 citation statements)
references
References 45 publications
16
198
1
3
Order By: Relevance
“…Studies of both ulnar and tibial loading in mice have been shown to decrease levels of the sclerostin protein expression, whereas unloading has been shown to increase levels of sclerostin [63]. These changes are highly correlated with sites of anabolic bone formation in the loading models [63][64][65][66]. Taken all together, these studies highlight the essential role of osteocytes in both immediate mechanosensation and the coordination of later adaptive responses.…”
Section: Tissue-level Adaptationmentioning
confidence: 86%
“…Studies of both ulnar and tibial loading in mice have been shown to decrease levels of the sclerostin protein expression, whereas unloading has been shown to increase levels of sclerostin [63]. These changes are highly correlated with sites of anabolic bone formation in the loading models [63][64][65][66]. Taken all together, these studies highlight the essential role of osteocytes in both immediate mechanosensation and the coordination of later adaptive responses.…”
Section: Tissue-level Adaptationmentioning
confidence: 86%
“…cell signaling | electrophysiology | mechanotransduction | junctional conductance I ncreasing evidence indicates that bone homeostasis and osteogenic remodeling require mechanical loading of whole bone tissue (1)(2)(3)(4). Interstitial fluid in bone passes through hierarchical levels of porosity when bone tissue is deformed by external loads.…”
mentioning
confidence: 99%
“…For that reason, the addition of finite element analysis models has been crucial in enabling us to understand the strain field engendered on bone for the various animal loading modalities. Numerous studies have explored strain distributions under the loading regimes, each involving increasingly more sophisticated models [65][66][67][68][69][70][71][72]. Digital image correlation (DIC) has also been used to assess surface strains experimentally.…”
Section: Extrinsic Factors Influencing Bone Formation Responsementioning
confidence: 99%